The Effect of the Effectiveness of the Family Hope Program on Poverty Reduction in Sorkam Kanan Village, West Sorkam District, Central Tapanuli Regency - Nurul Dalimunte (IHSA Institute, 2022)
Poverty is one of the problems experienced by developing countries, including Indonesia. Efforts to reduce poverty in Indonesia have been carried out by the government in every era of government with various poverty alleviation programs that aim to break the chain of poverty and improve the welfare and economy of the people in Indonesia. This study aims to determine whether there is an effect of the Effectiveness of the Family Hope Program on Poverty Reduction in Sorkam Kanan Village, West Sorkam District. The method used in this study using quantitative methods. The data sources include primary data and secondary data. Data collection techniques in the field, obtained by means of interviews, observation and questionnaires. It can be concluded that this study uses the product moment correlation test which is distributed to respondents with the results of r = 0.611. These results indicate that the effectiveness of the family of hope program in reducing poverty in the Sorkam right sub-district, West Sorkam sub-district is quite strong. Meanwhile, the results of the significant correlation coefficient test are t = 5, 319. From the test results, it can be concluded that there is a positive and significant influence between the hopeful family program on poverty reduction in Sorkam Kanan Village, West Sorkam District . While the advice offered by the researcher is that PKH participants are expected to attend every meeting held by the PKH supervisor so as to increase public knowledge about the goals and benefits of the assistance received